Students’ Attitude Towards English Language Learning Of 3rd Grade Students - Moh Rahdi Al- Hafiz; Alma Cita Calimbo; Mohamed Jlassi (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to explore and describe the attitudes of 3rd grade students at SMP Nasional Makassar towards learning English as a foreign language, specifically through affective, behavioral, and cognitive aspects of language attitude. Methodology: A descriptive-quantitative approach was used. The data were gathered using a 30-item questionnaire adapted from Abidin et al. (2012), divided into affective, behavioral, and cognitive domains. The instrument employed a five-point Likert scale. Validity and reliability tests were conducted using Excel and correlation analysis. The sample consisted of 90 students selected via quota sampling. Main Findings: The findings show that students have predominantly positive attitudes toward English learning. The mean score reached 94.8, well above the threshold of 70, indicating strong agreement in aspects such as enjoyment, confidence, and the belief that English enhances academic and social development. Affective, behavioral, and cognitive responses supported this positive orientation Novelty/Originality of this study: This study provides empirical insight into the emotional, behavioral, and mental orientations of junior high school students toward English, contributing data from an underrepresented school context in Indonesia. It integrates Islamic values as motivational context and offers a framework for improving curriculum and teaching methods that align with students’ psychological readiness.